An integrated project management methodology under a social perspective in industrialisation projects. (23rd February 2023) - Tereso, Anabela; Fernandes, Gabriela; Araújo, Madalena; Oliveira, Catarina; Ruão, Teresa; Lopes, Ana Isabel; Faria, João
This paper presents an integrated methodology for managing industrialisation projects combining know-how, abilities, instruments, and project management tools and techniques to fulfil more efficiently and effectively industrialisation requirements. Different research methods were used during an in-depth case study involving seven researchers over three years at an automotive industry company. Firstly, internal documents related to the organisation's specific set of rules for project management were analysed. Secondly, the organisation project managers' activities were observed. Thirdly, unstructured interviews were conducted to assess the organisation's project management awareness and the actual usage of tools and techniques. Finally, workflows were designed to represent the AS-IS model and the proposed TO-BE model. The methodology integrates a social project management approach, with social media tools, to improve communication between the industrialisation project management teams. Social project management is used to smoothly increase the projects' awareness and management within the global social ecosystem of the organisation.